“Hair!”: Remnants of Ascetic Exegesis in Augustine of Hippo’s De Opere Monachorum - Doerfler, Maria E. (Journal of early Christian studies, 2014)
Augustine of Hippo’s De opere monachorum directs itself against itinerant ascetics who, in emulation of the apostolic ideal, sought to support themselves by begging rather than manual labor. The treatise attests to a struggle not only over the legitimacy of different forms of ascetic practice, but over matters of exegesis. The latter is evident particularly in Augustine’s emphatic assertion that the wandering monks’ long hair, intended to identify its bearers as having embraced sexual continence, reflected misguided scriptural reading practices. This essay explores Augustine’s and his opponents’ approaches to biblical interpretation, its deployment to construct and deconstruct different visions of ascetic formation, and the conflicting theories of sexuality and eschatology reflected therein.